Graft healing in anterior cruciate ligament reconstruction - Chen Chih-Hwa (BMC, 2009)
Abstract Successful anterior cruciate ligament reconstruction with a tendon graft necessitates solid healing of the tendon graft in the bone tunnel. Improvement of graft healing to bone is crucial for facilitating an early and aggressive rehabilitation and ensuring rapid return to pre-injury levels activity. Tendon graft healing in a bone tunnel requires bone ingrowth into the tendon. Indirect Sharpey fiber formation and direct fibrocartilage fixation confer different anchorage strength and interface properties at the tendon-bone interface. For enhancing tendon graft-to-bone healing, we introduce a strategy that includes the use of periosteum, hydrogel supplemented with periosteal progenitor cells and bone morphogenetic protein-2, and a periosteal progenitor cell sheet. Future studies include the use of cytokines, gene therapy, stem cells, platelet-rich plasma, and mechanical stress for tendon-to-bone healing. These strategies are currently under investigation, and will be applied in the clinical setting in the near future.